Study on Optimization of Stope Structural Parameters and Filling Scheme of Wawu Phosphate Mine in Yichang City, China - Peng, Gao; Gaoyi, Dong; Jingsong, Chen; Zhou, Chunmei; Manqing, Lin; Weizhong, Zhang; Yang, Sun (Frontiers in Earth Science, 2022)
Reasonable stope structural parameters are very important to ensure the safety and efficiency of mining. In this paper, based on the elastic-plastic constitutive model of Mohr-Coulomb strength criterion, the reasonable span and critical span are calculated by using simply supported beam theory and mine room width calculation formula. PLAXIS2D finite element analysis software was used to conduct numerical simulation research on 7×9m and 5×12m stope structure parameter schemes and 7×9m and 5×12m waste rock filling schemes. The optimal structure parameters of the stope were determined based on the calculation and analysis of displacement variation rule, surrounding rock stress distribution and plastic zone. The analysis and simulation results show that when the stope span is 9m and the waste rock is filled, the change of the maximum vertical displacement, the maximum principal stress and the volume of the plastic zone are small, the plastic zone is not connected, and the stope is in a stable state. Comprehensively considering the calculation results of the model, when the stope span is 9m and waste rock is filled, it can give full play to the stope production capacity and maximize the interests of the mine on the premise of ensuring the stope safety.